2015
DOI: 10.1175/jhm-d-14-0191.1
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Canadian Precipitation Analysis (CaPA)

Abstract: This paper presents an assessment of the operational system used by the Meteorological Service of Canada for producing near-real-time precipitation analyses over North America. The Canadian Precipitation Analysis (CaPA) system optimally combines available surface observations with numerical weather prediction (NWP) output in order to produce estimates of precipitation on a 15-km grid at each synoptic hour (0000, 0600, 1200, and 1800 UTC). The validation protocol used to assess the quality of the CaPA has demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 35 publications
4
126
0
Order By: Relevance
“…A number of limited-area precipitation analysis systems based on the univariate optimum interpolation algorithm are described, for example, in Bhargava and Danard (1994), Ha¨ggmark et al (2000), Mahfouf et al (2007) and recently in Lespinas et al (2015). Conceptually, the systems differ through the choice of the variable defined to carry out the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of limited-area precipitation analysis systems based on the univariate optimum interpolation algorithm are described, for example, in Bhargava and Danard (1994), Ha¨ggmark et al (2000), Mahfouf et al (2007) and recently in Lespinas et al (2015). Conceptually, the systems differ through the choice of the variable defined to carry out the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was also applied at ECMWF by Lopez (2011) in their 4D-Var data assimilation system. Recently, Lespinas et al (2015) presented an assessment of the operational Canadian precipitation analysis system [initially developed by Mahfouf et al (2007)] in which the analysis is performed on a cubic-root transformed variable as proposed by Fortin (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we compare simulated precipitation (Fig. 2) to the regional deterministic configuration of the Canadian Precipitation Analysis (CaPA-RDPA; Lespinas et al 2015). We used version 4.0 (v4.0) of CaPA; in addition to the gauge networks identified in Lespinas et al (2015), CaPA v4.0 assimilates Canadian and U.S. radar data following Fortin et al (2015).…”
Section: Verifying Observationsmentioning
confidence: 99%
“…They found that driving the model with an early experimental version of CaPA (Mahfouf et al 2007) versus precipitation simulated by a regional version of GEM with a 15-km horizontal resolution (Mailhot et al 2006) degraded the Nash-Sutcliffe model efficiency coefficient for Lake Erie but improved it by 0.06 for Lake Ontario. Deficiencies found in this early version of the analysis (Carrera et al 2010) (Lespinas et al 2015). In version 3.0, the assimilation of radar data was added .…”
Section: Model Verificationmentioning
confidence: 99%
“…Two precipitation datasets were used as input: the Canadian Precipitation Analysis (CaPA; Lespinas et al, 2015), and a Thiessen polygon interpolation of the Global Historical Climatology Network -Daily (GHCND; Menne et al, 2012). CaPA is a near-real-time quantitative precipitation estimate product from ECCC that is available on a 10 km grid for all of North America (http://collaboration.cmc.ec.gc.ca/cmc/cmoi/ product_guide/submenus/capa_e.html).…”
Section: Introductionmentioning
confidence: 99%